Sexual harassment in institutions of higher learning: adequacy of the provisions in Universiti Teknologi MARA (UiTM) / Farah Afiqah Nordin, Farha Nabiha Mustaffa and Aminu Razif Zainal Ariffin - Nordin, Farah Afiqah; Mustaffa, Farha Nabiha; Zainal Ariffin, Aminu Razif (2011)
This study, "Sexual Harassment in Institutions of Higher Learning: Adequacy of the Provisions in Universiti Teknologi MARA ", is completed as a fulfilment of the course of Bachelor of Legal Studies (Hons). This study was conducted mainly in UiTM Shah Alam in order to analyse the adequacy of UiTM's provision in handling sexual harassment complaints occurred among its students and staff. This research adopted several methods in order to fulfil the objectives of the research. The methods applied were qualitative research that relied on a library-based research that were gathered from statutes, text books, journals, articles both from the shelves and also on the internet. The researchers have conducted semi-structured interviews with Professor Emeritus Datuk Dr. Shad Saleem Faruqi, a Legal Advisor of UiTM and Puan Rokiah bt. Mahmood, a Counsellor at the Counselling Unit in order to obtain a clearer opinion on the provisions and procedures of UiTM. Apart from that, the researchers have also studied the Acts and policies from other local university mainly University of Malaya and also from other foreign countries mainly United Kingdom, Australia and Canada for the purpose of comparison. Overall, it is found that UiTM did not have a specific provision or policy to govern sexual harassment and that the current provisions are not sufficient in dealing with this issue. At the end of the research, we provided recommendations in order to create a specific policy in curbing sexual harassment problem in UiTM Malaysia.